2016
DOI: 10.20525/ijfbs.v5i1.41
|View full text |Cite
|
Sign up to set email alerts
|

Risk Pricing in Emerging Economies

Abstract: Iran’s banking industry as a developing country is comparatively very new to risk management practices. An inevitable predictive implication of this rapid growth is the growing concerns with regard to credit risk management which is the motivation of conducting this research. The paper focuses on the credit scoring aspect of credit risk management using both logit and probit regression approaches. Real data on corporate customers are available for conducting this research which is also a contribution to this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…The organization makes available for individuals and companies for their knowledge and use when considering any investments, lending, or borrowing activities. The company is run by its Board of Directors and a team of management, under whom employees operate the functions and processes of the company (Anagnostopoulos & Abedi, 2016).…”
Section: • Credit Bureaumentioning
confidence: 99%
See 2 more Smart Citations
“…The organization makes available for individuals and companies for their knowledge and use when considering any investments, lending, or borrowing activities. The company is run by its Board of Directors and a team of management, under whom employees operate the functions and processes of the company (Anagnostopoulos & Abedi, 2016).…”
Section: • Credit Bureaumentioning
confidence: 99%
“…However, it was found that Islamic bank managers' information about the AECB credit scoring procedure is inadequate, although they are using its credit scoring as a supplement to assess their customers' creditworthiness, which may hinder acceptance of AECB credit rating services fully. In addition to internalizing AECB techniques, Islamic banks use their own rules and methods, including 6Cs, which are more character-oriented in the lending decision which helps them cover the demerit of objective methods (Anagnostopoulos, & Abedi, 2016;Masood et al, 2012). Although Islamic banks apply the AECB approach to avoid non-performing and defaulted loans, defaults happen as they are behavioral and might be rooted in not providing consolidated accounting figures (Anagnostopoulos & Abedi, 2016).…”
Section: Al Etihad Credit Bureau's Performance In the United Arab Emi...mentioning
confidence: 99%
See 1 more Smart Citation